Mediatization, Religion, and Human Rights: A perspective through the television program “The right to have an opinion” - Burcea, Nelu (Anais de Resumos Expandidos do Seminário Internacional de Pesquisas em Midiatização e Processos Sociais; v. 1 n. 1 (2016): Anais de Resumos Expandidos I Seminário Internacional de Pesquisas em Midiatização e Processos Sociais, 2019)
---